Viability of endolithic micro-organisms in rocks from the McMurdo Dry Valleys of Antarctica established by confocal and fluorescence microscopy - Wierzchos, Jacek; Ríos, Asunción de los; Sancho, Leopoldo G.; Ascaso, Carmen (Journal of Microscopy, 2004)
5 pages, and 1 figure. The rocks of the McMurdo Dry Valleys desert in Antarctica harbour endolithic communities of micro-organisms such as lichens, fungi, cyanobacteria and bacteria. Establishing the physiological status and viability of these microbial colonies in their natural microhabitat has far-reaching implications for understanding the microbial ecology of the harsh environment of this polar desert. Here we describe the use of confocal microscopy and a specific fluorescent probe (FUN-1) to evaluate the metabolic activity of fungal cells. Application of confocal microscopy also served to identify living and dead bacteria or cyanobacteria using the fluorescent assay reagents Live/Dead SYTO 9 and propidium iodide or SYTOX Green, respectively. In addition, through the use of epifluorescence microscopy, live/dead bacteria and cyanobacteria could be detected by estimating fluorescence from their cell components provoked by simultaneously staining with nucleic acids stains such as DAPI and SYTOX Green. Peer reviewed